PCBP1 interacts with the HTLV-1 Tax oncoprotein to potentiate NF-κB activation - Su, Rui; Kang, Xue; Niu, Yifan; Zhao, Tiesuo; Wang, Hui (Frontiers in Immunology, 2024)
Human T-cell leukemia virus type 1 (HTLV-1) is the etiological agent of adult T-cell leukemia/lymphoma (ATL) and the neurological disease HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). As a transactivator/oncoprotein, HTLV-1 Tax dysregulates the cellular processes to constitutively activate NF-κB signaling pathway, thereby promoting the survival and transformation of HTLV-1infected T cells. Despite extensive study of Tax, how Tax interacts with host factors to regulate NF-κB activation and HTLV-1-diven cell proliferation is not entirely clear.Here, we showed that overexpression of Poly (rC)-binding protein 1 (PCBP1) promoted Tax-mediated IκB kinase (IKK)-NF-κB signaling activation, whereas knockdown of PCBP1 attenuated Tax-dependent IKK-NF-κB activation. However, Tax activation of HTLV-1 long terminal repeats (LTR) was unaffected by PCBP1. Furthermore, depletion of PCBP1 led to apoptosis and reduced proliferation of HTLV-1-transformed cells.Mechanistically, PCBP1 interacted and co-localized with Tax in the cytoplasm, and PCBP1 KH3 domain was indispensable for the interaction between PCBP1 and Tax.Moreover, PCBP1 facilitated the assembly of Tax/IKK complex. Collectively, our results demonstrated that PCBP1 may exert an essential effect in Tax/IKK complex combination and subsequent NF-κB activation, which provides a novel insight into the pathogenetic mechanisms of HTLV-1.